Oxide-molecular sieve series catalyst and application thereof

By using mechanical mixing and hydrothermal method to synthesize nano-scale metal oxides and short-b-axis zeolite molecular sieves in the oxide/molecular sieve tandem catalyst, the problems of low aromatic yield and high CO selectivity in the process of carbon dioxide preparation of aromatic hydrocarbons are solved, and catalytic performance with high activity, high selectivity and long life are achieved.

CN119565587APending Publication Date: 2025-03-07WUHAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411751328.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07

Smart Images

  • Figure BDA0005165066900000191
    Figure BDA0005165066900000191
Patent Text Reader

Abstract

The invention discloses an oxide-molecular sieve series catalyst and application thereof. The catalyst comprises a metal oxide and a molecular sieve which are mechanically mixed, wherein the mass ratio of the metal oxide to the molecular sieve is 1: (1-3); wherein the metal oxides comprise at least two of a zirconium-based oxide, a zinc-based oxide and an indium-based oxide, and the mass ratio of each metal oxide is any ratio; the metal oxide is synthesized by adopting a hydrothermal method, and an organic epoxy compound is added in the hydrothermal method synthesis process of the metal oxide; the molecular sieve is synthesized by a hydrothermal method, and a b-axis regulator of the molecular sieve is added in the hydrothermal synthesis process of the molecular sieve. The catalyst provided by the invention can catalytically reduce carbon dioxide to synthesize aromatic hydrocarbon with high activity and high selectivity under relatively low CO selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an oxide-molecular sieve tandem catalyst and its application. Background Art

[0002] Using thermal catalytic reduction technology to reduce carbon dioxide into high-value-added chemicals such as methanol, low-carbon alcohols, olefins and aromatics is one of the main measures to recycle carbon dioxide resources. Among them, aromatics are important chemical raw materials and basic products. They are currently mainly produced by petroleum cracking. However, due to environmental problems, the use of carbon dioxide to produce aromatics has the advantages of cleanliness and efficiency, which is of great significance to energy security, energy conservation and emission reduction.

[0003] Oxide / molecular sieve tandem catalysts have good performance in methanol synthesis (MS) and methanol to hydrocarbons (MTH) reactions, and are good materials for hydrogenating carbon dioxide to produce aromatics. However, due to the chemical inertness of CO2 molecules and the complexity of the reaction network, most oxide / molecular sieve tandem systems currently still face the problems of low aromatic yield (≤8%) and high CO selectivity (34-71%) [J.Mater.Chem.A 2023, 11, 17938-17960; Chem 2021, 7, 2277-2311]. Improving the high-temperature methanol synthesis rate and the coverage of methanol / methoxy species through the rational design of catalysts is a good strategy to improve catalytic performance, but there is an essential difference between methanol synthesis and aromatics synthesis. Therefore, the preparation method of CO2 hydrogenation tandem catalysts with high aromatics synthesis activity still needs further exploration. In addition, the selectivity of CO in the product needs to be further reduced. Summary of the invention

[0004] In order to solve the above problems, the present application proposes an oxide-molecular sieve tandem catalyst, comprising a mechanically mixed metal oxide and a molecular sieve; wherein the mass ratio of the metal oxide to the molecular sieve is 1:1-3;

[0005] The metal oxide comprises at least two of zirconium-based oxide, zinc-based oxide and indium-based oxide, and the mass ratio of each metal oxide is any ratio; the metal oxide is synthesized by hydrothermal method, and an organic epoxy compound is added during the hydrothermal synthesis of the metal oxide;

[0006] The molecular sieve is synthesized by hydrothermal method, and a molecular sieve b-axis regulator is added during the hydrothermal synthesis of the molecular sieve. The metal oxide prepared in the present application is a nano-scale oxide, and the surface is rich in oxygen vacancies and / or metal-O-metal interface species, which increases the stability of active species and the catalytic dissociation of hydrogen activity and the ability to activate carbon dioxide; the prepared molecular sieve material is a zeolite molecular sieve material with a short b axis, which promotes the diffusion and conversion rate of active intermediate species. The combination of the advantages of the two is conducive to the high-activity catalytic carbon dioxide reduction reaction to obtain aromatics; at the same time, it also makes the catalyst have a longer service life, and can catalyze the reduction of carbon dioxide to synthesize aromatics with high activity and high selectivity at low CO selectivity.

[0007] Preferably, the metal oxides include zirconium-based oxides, zinc-based oxides and indium-based oxides, wherein the mass ratio of zirconium, zinc and indium in the zirconium-based oxides, zinc-based oxides and indium-based oxides is 111:6-12:11.

[0008] Preferably, the zirconium precursor of the zirconium-based oxide is one of zirconium nitrate, zirconium oxychloride, zirconium chloride, zirconium sulfate, zirconium nitrate pentahydrate, zirconium oxychloride octahydrate, zirconium sulfate tetrahydrate, or a mixture of two or more thereof in any proportion;

[0009] The zinc precursor of the zinc-based oxide is one of zinc nitrate, zinc acetate, zinc sulfate, zinc nitrate hexahydrate, zinc acetate dihydrate, and zinc sulfate heptahydrate, or a mixture of two or more of them in any proportion;

[0010] The indium precursor of the indium-based oxide is one of indium sulfate, indium acetate, indium trichloride, indium nitrate pentahydrate, indium chloride tetrahydrate, or a mixture of two or more of them in any proportion;

[0011] The organic epoxy compound is at least one of epichlorohydrin, propylene oxide, butylene oxide, dioxane, and tetrahydrofuran, or a mixture of two or more thereof in any proportion;

[0012] The molecular sieve b-axis regulator is at least one of ammonium fluoride and behenyltrimethylammonium methyl sulfate or a mixture of the two in any proportion.

[0013] Preferably, the mechanical mixing method is powder mixing, particle mixing or grinding mixing.

[0014] Preferably, the metal oxide is synthesized as follows:

[0015] The metal oxide precursor is dissolved in a solvent, and an organic epoxy compound is added to react, and a solution I is obtained after the reaction is completed;

[0016] The solution I is subjected to a hydrothermal reaction, and the hydrothermal reaction product is dried, crushed, and calcined to obtain an oxide material.

[0017] Preferably, the molar ratio of the organic epoxy compound to the metal element of the metal oxide is 1.5-2.5:1;

[0018] The temperature of the hydrothermal reaction of adding the organic epoxy compound is 10-40°C, and the reaction time is 0-1h;

[0019] The temperature of the hydrothermal reaction of solution I is 100-200°C, and the reaction time is 15-25h; the temperature of the calcination is 400-600°C, and the time is 3-10h;

[0020] During the preparation of solution I, if there is an indium-based oxide precursor, a zirconium-based oxide precursor and a zinc-based oxide precursor are added first, and then an organic epoxy compound is added for reaction before adding the indium-based oxide precursor.

[0021] Preferably, the molecular sieve is synthesized as follows:

[0022] The organic template is added into water, and then the silicon precursor, the aluminum precursor and the molecular sieve b-axis regulator are added to react, and after the reaction is completed, a solution II is obtained;

[0023] The solution II is subjected to a hydrothermal reaction, and the hydrothermal reaction product is dried, crushed, and calcined to obtain a molecular sieve.

[0024] Preferably, the organic template is one of tetrapropylammonium hydroxide and tetraethylammonium hydroxide or a mixture of the two in any proportion;

[0025] The silicon precursor is at least one of tetraethyl silicate (TEOS), 25wt% silica sol and 40wt% silica sol, or a mixture of two or more in any proportion;

[0026] The aluminum precursor is at least one of aluminum isopropoxide, aluminum sulfate, aluminum chloride and aluminum oxide, or a mixture of two or more of them in any proportion.

[0027] Preferably, in terms of molar ratio, the ratio of the organic template, the molecular sieve b-axis regulator, the Si element in the silicon precursor, and the aluminum element in the aluminum precursor is 130-160:0-160:100:1; the temperature for the mixed reaction is 10-40°C, and the reaction time is 6-18h;

[0028] The temperature of the hydrothermal reaction of solution II is 150-220° C., and the reaction time is 24-96 hours; the temperature of the calcination is 500-600° C., and the time is 3-10 hours.

[0029] On the other hand, the application of oxide-molecular sieve tandem catalyst in the preparation of aromatics by carbon dioxide reduction is also disclosed, with a CO2 conversion rate of not less than 11.9%, a CO selectivity of not more than 24.3%, and an aromatics selectivity of not less than 75.2%. The high-performance oxide / molecular sieve tandem catalyst material provided by the present application has the advantages of significantly improving the selectivity of aromatics in the product and reducing the selectivity of low-carbon products such as CO and methane; the raw materials used in the preparation method are simple and easy to obtain, the process is simple and safe, and the product has good reproducibility.

[0030] This application can bring the following beneficial effects:

[0031] 1. The metal oxide prepared in the present application is a nano-scale oxide, and its surface is rich in oxygen vacancies and / or metal-O-metal interface species, which increases the stability of active species and the catalytic dissociation activity of hydrogen and the ability to activate carbon dioxide; the prepared molecular sieve material is a short b-axis zeolite molecular sieve material, which promotes the diffusion and conversion rate of active intermediate species. The combination of the advantages of the two is conducive to the high-activity catalytic reduction of carbon dioxide to prepare aromatic hydrocarbons; at the same time, it also makes the catalyst have a longer service life, and can catalyze the reduction of carbon dioxide to synthesize aromatic hydrocarbons with high activity and high selectivity at low CO selectivity.

[0032] 2. The high-performance oxide / molecular sieve tandem catalyst material provided in this application has the advantages of significantly improving the selectivity of aromatics in the product while reducing the selectivity of low-carbon products such as CO and methane; the raw materials used in its preparation method are simple and easy to obtain, the process is simple and safe, and the prepared products have good reproducibility.

[0033] 3. The highly catalytically active oxide / molecular sieve tandem catalytic material provided by the present invention is suitable for catalytically hydrogenating carbon dioxide to produce aromatics. The carbon dioxide can be derived from an industrial tail gas carbon dioxide mixture, and the hydrogen can be derived from renewable energy - green hydrogen produced by electrolysis of water and / or gray hydrogen in coal chemical industry and petrochemical industry. This can alleviate the pressure of carbon dioxide emissions, while producing high value-added chemicals and generating economic benefits. DETAILED DESCRIPTION

[0034] In order to clearly illustrate the technical features of this solution, this application is elaborated in detail below through specific implementation methods.

[0035] An oxide-molecular sieve series catalyst, comprising a mechanically mixed metal oxide and a molecular sieve; wherein the mass ratio of the metal oxide to the molecular sieve is 1:1-3;

[0036] The metal oxide comprises at least two of zirconium-based oxide, zinc-based oxide and indium-based oxide, and the mass ratio of each metal oxide is any ratio; the metal oxide is synthesized by hydrothermal method, and an organic epoxy compound is added during the hydrothermal synthesis of the metal oxide;

[0037] The molecular sieve is synthesized by a hydrothermal method, and a molecular sieve b-axis regulator is added during the hydrothermal synthesis of the molecular sieve.

[0038] The metal oxides include zirconium-based oxides, zinc-based oxides and indium-based oxides, wherein the mass ratio of zirconium, zinc and indium in the zirconium-based oxides, zinc-based oxides and indium-based oxides is 111:6-12:11.

[0039] The zirconium precursor of the zirconium-based oxide is one of zirconium nitrate, zirconium oxychloride, zirconium chloride, zirconium sulfate, zirconium nitrate pentahydrate, zirconium oxychloride octahydrate, and zirconium sulfate tetrahydrate, or a mixture of two or more of them in any proportion;

[0040] The zinc precursor of the zinc-based oxide is one of zinc nitrate, zinc acetate, zinc sulfate, zinc nitrate hexahydrate, zinc acetate dihydrate, and zinc sulfate heptahydrate, or a mixture of two or more of them in any proportion;

[0041] The indium precursor of the indium-based oxide is one of indium sulfate, indium acetate, indium trichloride, indium nitrate pentahydrate, indium chloride tetrahydrate, or a mixture of two or more of them in any proportion;

[0042] The organic epoxy compound is at least one of epichlorohydrin, propylene oxide, butylene oxide, dioxane, and tetrahydrofuran, or a mixture of two or more thereof in any proportion;

[0043] The molecular sieve b-axis regulator is at least one of ammonium fluoride and behenyltrimethylammonium methyl sulfate or a mixture of the two in any proportion.

[0044] The mechanical mixing method is powder mixing, particle mixing or grinding mixing.

[0045] The metal oxide is synthesized as follows:

[0046] The metal oxide precursor is dissolved in a solvent, and an organic epoxy compound is added to react, and a solution I is obtained after the reaction is completed;

[0047] The solution I is subjected to a hydrothermal reaction, and the hydrothermal reaction product is dried, crushed, and calcined to obtain an oxide material.

[0048] The molar ratio of the organic epoxy compound to the metal element of the metal oxide is 1.5-2.5:1;

[0049] The temperature of the hydrothermal reaction of adding the organic epoxy compound is 10-40°C, and the reaction time is 0-1h;

[0050] The temperature of the hydrothermal reaction of solution I is 100-200°C, and the reaction time is 15-25h; the temperature of the calcination is 400-600°C, and the time is 3-10h;

[0051] During the preparation of solution I, if there is an indium-based oxide precursor, a zirconium-based oxide precursor and a zinc-based oxide precursor are added first, and then an organic epoxy compound is added for reaction before adding the indium-based oxide precursor.

[0052] The molecular sieve is synthesized as follows:

[0053] The organic template is added into water, and then the silicon precursor, the aluminum precursor and the molecular sieve b-axis regulator are added to react, and after the reaction is completed, a solution II is obtained;

[0054] The solution II is subjected to a hydrothermal reaction, and the hydrothermal reaction product is dried, crushed, and calcined to obtain a molecular sieve.

[0055] The organic template is one of tetrapropylammonium hydroxide and tetraethylammonium hydroxide or any ratio of the two;

[0056] The silicon precursor is at least one of tetraethyl silicate, 25wt% silica sol and 40wt% silica sol, or a mixture of two or more in any proportion;

[0057] The aluminum precursor is at least one of aluminum isopropoxide, aluminum sulfate, aluminum chloride and aluminum oxide, or a mixture of two or more of them in any proportion.

[0058] In terms of molar ratio, the ratio of the organic template, the molecular sieve b-axis regulator, the Si element in the silicon precursor, and the aluminum element in the aluminum precursor is 130-160:0-160:100:1; the temperature for the mixed reaction is 10-40°C, and the reaction time is 6-18h;

[0059] The temperature of the hydrothermal reaction of solution II is 150-220° C., and the reaction time is 24-96 hours; the temperature of the calcination is 500-600° C., and the time is 3-10 hours.

[0060] The application of the oxide-molecular sieve tandem catalyst prepared in the present application in the preparation of aromatics by reduction of carbon dioxide has a CO2 conversion rate of not less than 11.9%, a CO selectivity of not more than 24.3%, and an aromatics selectivity of not less than 75.2%.

[0061] Example 1

[0062] 5.2217 g of zirconium nitrate pentahydrate and 0.5465 g of zinc nitrate hexahydrate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min under a frequency of 50 kHz, 2 mL of dioxane was added and reacted at 25° C. for 2 min to obtain a solution I;

[0063] The solution I was subjected to a hydrothermal reaction at 150°C for 20 hours. After the reaction was completed, the hydrothermal reaction product was dried and crushed, and then calcined at 500°C for 4 hours to obtain a powdered ZnZrO x Oxide materials;

[0064] 20 g of tetrapropylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 14 g of TEOS, 0.145 g of aluminum isopropoxide and 3.25 g of ammonium fluoride, and the mixture was stirred at 25 °C for 12 h to obtain solution II;

[0065] The solution II is subjected to a hydrothermal reaction at 180° C. for 48 hours. After the reaction is completed, the hydrothermal reaction product is dried and crushed, and then calcined at 550° C. for 4 hours to obtain a ZSM-5 molecular sieve material;

[0066] 0.15 g of oxide and 0.3 g of molecular sieve material were ground and mixed, and then granulated into 40-60 mesh to obtain a series catalytic material, which was recorded as catalyst 1#.

[0067] Example 2

[0068] 2.8345 g of zirconium chloride and 0.3370 g of zinc acetate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min under a frequency of 50 kHz, 2 mL of propylene oxide was added and reacted at 25° C. for 0 min to obtain a solution I;

[0069] The solution I was subjected to a hydrothermal reaction at 150°C for 20 hours. After the reaction was completed, the hydrothermal reaction product was dried and crushed, and then calcined at 500°C for 4 hours to obtain a powdered ZnZrO x Oxide materials;

[0070] 14.4863 g of tetraethylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 16.1508 g of silica sol (25 wt %), 0.1215 g of aluminum sulfate and 1.625 g of behenyltrimethylammonium methylsulfate, and the mixture was stirred at 25° C. for 12 h to obtain a solution II;

[0071] The solution II is subjected to ZSM-5 molecular sieve material at 180°C;

[0072] 0.15g oxide and 0.3g of fraction were hydrothermally reacted for 48h. After the reaction, the hydrothermal reaction product was dried and crushed, and calcined at 550°C for 4h to obtain the sub-sieve material, which was ground and mixed, and pressed into 40-60 mesh granules to obtain a series catalytic material, recorded as catalyst 2#.

[0073] Example 3

[0074] 2.8345 g of zirconium chloride and 0.1685 g of zinc acetate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution at a frequency of 50 kHz for 30 min, 2 mL of epichlorohydrin was added and reacted at 10° C. for 1 h to obtain a solution I, and then 0.2377 g of indium sulfate was added;

[0075] The solution I was subjected to a hydrothermal reaction at 150°C for 20 hours. After the reaction was completed, the hydrothermal reaction product was dried and crushed, and then calcined at 500°C for 4 hours to obtain powdered In-ZnZrO x Oxide materials;

[0076] 14.4863 g of tetraethylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 16.1508 g of silica sol (25 wt %), 0.1215 g of aluminum sulfate and 3.25 g of ammonium fluoride, and the mixture was stirred at 25° C. for 12 h to obtain a solution II;

[0077] The solution II is subjected to ZSM-5 molecular sieve material at 180°C;

[0078] 0.15g oxide and 0.3g fraction were hydrothermally reacted for 48h. After the reaction, the hydrothermal reaction product was dried and crushed, and calcined at 550°C for 4h to obtain the sub-sieve material, which was ground and mixed, and pressed into 40-60 mesh granules to obtain a series catalytic material, recorded as catalyst 3#.

[0079] Example 4

[0080] 2.8345 g of zirconium chloride and 0.337 g of zinc acetate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution at a frequency of 50 kHz for 30 min, 2 mL of propylene oxide was added and reacted at 25° C. for 2 min to obtain a solution I, and then 0.2682 g of indium acetate was added;

[0081] The solution I was subjected to a hydrothermal reaction at 150°C for 20 hours. After the reaction was completed, the hydrothermal reaction product was dried and crushed, and then calcined at 500°C for 4 hours to obtain powdered In-ZnZrO x Oxide materials;

[0082] 14.4863 g of tetraethylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 16.1508 g of silica sol (25 wt %), 0.1215 g of aluminum sulfate and 3.25 g of ammonium fluoride, and the mixture was stirred at 25° C. for 12 h to obtain a solution II;

[0083] The solution II is subjected to ZSM-5 molecular sieve material at 180°C;

[0084] 0.15g oxide and 0.3g of the hydrothermal reaction were reacted for 48h. After the reaction, the hydrothermal reaction product was dried and crushed, and calcined at 550°C for 4h to obtain the sub-sieve material, which was ground and mixed, and pressed into 40-60 mesh granules to obtain a series catalytic material, recorded as catalyst 4#.

[0085] Example 5

[0086] 4.3230 g of zirconium sulfate tetrahydrate and 0.3479 g of zinc nitrate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min under a frequency of 50 kHz, 2 mL of dioxane was added and reacted at 40° C. for 2 min to obtain a solution I;

[0087] The solution I was subjected to a hydrothermal reaction at 200°C for 20 hours. After the reaction was completed, the hydrothermal reaction product was dried and crushed, and then calcined at 500°C for 4 hours to obtain a powdered ZnZrO x Oxide materials;

[0088] 20 g of tetrapropylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 14 g of TEOS, 0.145 g of aluminum isopropoxide and 2.1 g of behenyltrimethylammonium methylsulfate, and the mixture was stirred at 25 °C for 12 h to obtain solution II;

[0089] The solution II is subjected to a hydrothermal reaction at 180° C. for 48 hours. After the reaction is completed, the hydrothermal reaction product is dried and crushed, and then calcined at 550° C. for 4 hours to obtain a ZSM-5 molecular sieve material;

[0090] 0.3 g of oxide and 0.3 g of molecular sieve material were ground and mixed, and then granulated into 40-60 mesh to obtain a series catalytic material, which was recorded as catalyst 5#.

[0091] Example 6

[0092] 5.2217 g of zirconium nitrate pentahydrate and 0.4032 g of zinc acetate dihydrate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min under a frequency of 50 kHz, 2 mL of dioxane was added and reacted at 25° C. for 2 min to obtain a solution I;

[0093] The solution I was subjected to a hydrothermal reaction at 150°C for 20 hours. After the reaction was completed, the hydrothermal reaction product was dried and crushed, and then calcined at 400°C for 10 hours to obtain a powdered ZnZrO x Oxide materials;

[0094] 20 g of tetrapropylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 14 g of TEOS, 0.145 g of aluminum isopropoxide and 5 g of behenyltrimethylammonium methylsulfate, and the mixture was stirred at 25 °C for 12 h to obtain a solution II;

[0095] The solution II is subjected to a hydrothermal reaction at 180° C. for 48 hours. After the reaction is completed, the hydrothermal reaction product is dried and crushed, and then calcined at 550° C. for 4 hours to obtain a ZSM-5 molecular sieve material;

[0096] 0.15 g of oxide and 0.15 g of molecular sieve material were ground and mixed, and then granulated into 40-60 mesh to obtain a series catalytic material, which was recorded as catalyst 6#.

[0097] Example 7

[0098] 3.4465 g of zirconium sulfate and 0.5283 g of zinc sulfate heptahydrate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min under a frequency of 50 kHz, 2 mL of butylene oxide was added and reacted at 25° C. for 2 min to obtain a solution I;

[0099] The solution I was subjected to a hydrothermal reaction at 150°C for 20 hours. After the reaction was completed, the hydrothermal reaction product was dried and crushed, and then calcined at 500°C for 4 hours to obtain a powdered ZnZrO x Oxide materials;

[0100] 20 g of tetrapropylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 14 g of TEOS, 0.145 g of aluminum isopropoxide and 3.25 g of behenyltrimethylammonium methylsulfate, and the mixture was stirred at 25 °C for 12 h to obtain solution II;

[0101] The solution II is subjected to a hydrothermal reaction at 180° C. for 48 hours. After the reaction is completed, the hydrothermal reaction product is dried and crushed, and then calcined at 550° C. for 4 hours to obtain a ZSM-5 molecular sieve material;

[0102] 0.15 g of oxide and 0.3 g of molecular sieve material were ground and mixed, and then pressed into 40-60 mesh granules to obtain a series catalytic material, which was recorded as catalyst 7#.

[0103] Example 8

[0104] 5.2217 g of zirconium nitrate pentahydrate and 0.5465 g of zinc nitrate hexahydrate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min under a frequency of 50 kHz, 2 mL of tetrahydrofuran was added and reacted at 25° C. for 1 min to obtain a solution I;

[0105] The solution I was subjected to a hydrothermal reaction at 150°C for 20 hours. After the reaction was completed, the hydrothermal reaction product was dried and crushed, and then calcined at 500°C for 4 hours to obtain a powdered ZnZrO x Oxide materials;

[0106] 20 g of tetrapropylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 14 g of TEOS, 0.145 g of aluminum isopropoxide and 3.25 g of ammonium fluoride, and the mixture was stirred at 25 °C for 12 h to obtain solution II;

[0107] The solution II is subjected to a hydrothermal reaction at 180° C. for 48 hours. After the reaction is completed, the hydrothermal reaction product is dried and crushed, and then calcined at 550° C. for 4 hours to obtain a ZSM-5 molecular sieve material;

[0108] 0.15 g of oxide and 0.3 g of molecular sieve material were ground and mixed, and then pressed into 40-60 mesh granules to obtain a series catalytic material, which was recorded as catalyst 8#.

[0109] Example 9

[0110] 5.2217 g of zirconium nitrate pentahydrate and 0.5465 g of zinc nitrate hexahydrate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min at a frequency of 50 kHz, 2 mL of dioxane was added and reacted at 10° C. for 1 min to obtain a solution I;

[0111] The solution I was subjected to a hydrothermal reaction at 180°C for 15 hours. After the reaction was completed, the hydrothermal reaction product was dried and crushed, and then calcined at 600°C for 3 hours to obtain a powdered ZnZrO x Oxide materials;

[0112] 20 g of tetrapropylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 14 g of TEOS, 0.145 g of aluminum isopropoxide and 3.25 g of behenyltrimethylammonium methylsulfate, and the mixture was stirred at 10° C. for 6 h to obtain a solution II;

[0113] The solution II is subjected to a hydrothermal reaction at 150° C. for 24 hours. After the reaction is completed, the hydrothermal reaction product is dried and crushed, and calcined at 600° C. for 3 hours to obtain a ZSM-5 molecular sieve material;

[0114] 0.15 g of oxide and 0.3 g of molecular sieve material were ground and mixed, and then pressed into 40-60 mesh granules to obtain a series catalytic material, which was recorded as catalyst 9#.

[0115] Example 10

[0116] 5.2217 g of zirconium nitrate pentahydrate and 0.5465 g of zinc nitrate hexahydrate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min under a frequency of 50 kHz, 2 mL of tetrahydrofuran was added and reacted at 40° C. for 60 min to obtain a solution I;

[0117] The solution I was subjected to a hydrothermal reaction at 100°C for 25 hours. After the reaction was completed, the hydrothermal reaction product was dried and crushed, and then calcined at 400°C for 10 hours to obtain a powdered ZnZrO x Oxide materials;

[0118] 20 g of tetrapropylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 14 g of TEOS, 0.145 g of aluminum isopropoxide and 3.25 g of ammonium fluoride, and the mixture was stirred at 40 °C for 18 h to obtain solution II;

[0119] The solution II is subjected to a hydrothermal reaction at 220° C. for 48 hours. After the reaction is completed, the hydrothermal reaction product is dried and crushed, and calcined at 500° C. for 10 hours to obtain a ZSM-5 molecular sieve material;

[0120] 0.15 g of oxide and 0.3 g of molecular sieve material were ground and mixed, and then pressed into 40-60 mesh granules to obtain a series catalytic material, which was recorded as catalyst 10#.

[0121] Embodiment 11

[0122] 5.2217 g of zirconium nitrate pentahydrate and 0.5465 g of zinc nitrate hexahydrate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min under a frequency of 50 kHz, 2 mL of dioxane was added and reacted at 30° C. for 30 min to obtain a solution I;

[0123] The solution I was subjected to a hydrothermal reaction at 200°C for 20 hours. After the reaction was completed, the hydrothermal reaction product was dried and crushed, and then calcined at 500°C for 4 hours to obtain a powdered ZnZrO x Oxide materials;

[0124] 20 g of tetrapropylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 14 g of TEOS, 0.145 g of aluminum isopropoxide and 3.25 g of behenyltrimethylammonium methylsulfate, and the mixture was stirred at 30 °C for 15 h to obtain a solution II;

[0125] The solution II is subjected to a hydrothermal reaction at 200° C. for 48 hours. After the reaction is completed, the hydrothermal reaction product is dried and crushed, and calcined at 550° C. for 4 hours to obtain a ZSM-5 molecular sieve material;

[0126] 0.15 g of oxide and 0.3 g of molecular sieve material were ground and mixed, and then granulated into 40-60 mesh tablets to obtain a series catalytic material, which was recorded as catalyst 11#.

[0127] Example 12

[0128] 3.9197 g of zirconium oxychloride octahydrate and 0.5465 g of zinc nitrate hexahydrate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min under a frequency of 50 kHz, 2 mL of dioxane was added and reacted at 20° C. for 40 min to obtain a solution I;

[0129] The solution I was subjected to a hydrothermal reaction at 180°C for 25 hours. After the reaction, the hydrothermal reaction product was dried and crushed, and then calcined at 550°C for 8 hours to obtain a powdered ZnZrO x Oxide materials;

[0130] 20 g of tetrapropylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 14 g of TEOS, 0.145 g of aluminum isopropoxide and 3.25 g of ammonium fluoride, and the mixture was stirred at 30 °C for 12 h to obtain solution II;

[0131] The solution II is subjected to a hydrothermal reaction at 200° C. for 72 hours. After the reaction is completed, the hydrothermal reaction product is dried and crushed, and then calcined at 550° C. for 4 hours to obtain a ZSM-5 molecular sieve material;

[0132] 0.15 g of oxide and 0.3 g of molecular sieve material were ground and mixed, and then pressed into 40-60 mesh granules to obtain a series catalytic material, which was recorded as catalyst 12#.

[0133] Embodiment 13

[0134] 5.2217 g of zirconium nitrate pentahydrate and 0.5526 g of indium nitrate pentahydrate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min under a frequency of 50 kHz, 2 mL of dioxane was added and reacted at 20° C. for 40 min to obtain a solution I;

[0135] The solution I was subjected to a hydrothermal reaction at 180°C for 25 hours. After the reaction, the hydrothermal reaction product was dried and crushed, and then calcined at 550°C for 8 hours to obtain powdered InZrO x Oxide materials;

[0136] 20 g of tetrapropylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 14 g of TEOS, 0.145 g of aluminum isopropoxide and 3.25 g of behenyltrimethylammonium methylsulfate, and the mixture was stirred at 30° C. for 12 h to obtain a solution II;

[0137] The solution II is subjected to a hydrothermal reaction at 200° C. for 72 hours. After the reaction is completed, the hydrothermal reaction product is dried and crushed, and then calcined at 550° C. for 4 hours to obtain a ZSM-5 molecular sieve material;

[0138] 0.15 g of oxide and 0.3 g of molecular sieve material were ground and mixed, and then pressed into 40-60 mesh granules to obtain a series catalytic material, which was recorded as catalyst 13#.

[0139] Embodiment 14

[0140] 5.2217 g of zirconium nitrate pentahydrate and 0.5283 g of zinc sulfate heptahydrate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min under a frequency of 50 kHz, 2 mL of dioxane was added and reacted at 25° C. for 2 min to obtain a solution I;

[0141] The solution I was subjected to a hydrothermal reaction at 150°C for 20 hours. After the reaction was completed, the hydrothermal reaction product was dried and crushed, and then calcined at 500°C for 4 hours to obtain a powdered ZnZrO x Oxide materials;

[0142] 17.676 g of tetraethylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, and then 14 g of TEOS, 0.145 g of aluminum isopropoxide and 3.25 g of ammonium fluoride were added, and stirred at 25° C. for 12 h to obtain solution II; the solution II was subjected to a hydrothermal reaction at 180° C. for 48 h, and after the reaction, the obtained hydrothermal reaction product was dried and crushed, and calcined at 550° C. for 4 h to obtain HBeta molecular sieve material;

[0143] Mix 3g of hexamethyleneimine and 25.5mL of deionized water and stir for 30min, then add 14g of TEOS, 0.1164g of sodium aluminate and 3.25g of ammonium fluoride, and stir at 25°C for 12h to obtain solution II; the solution II is subjected to hydrothermal reaction at 170°C for 72h, and the hydrothermal reaction product obtained after the reaction is dried and crushed, and calcined at 550°C for 4h. Subsequently, the obtained solid is added to 50mL of ammonium chloride aqueous solution (1mol / L), stirred at 80°C for 3h for ion exchange treatment, exchanged three times, dried at 100°C overnight, and calcined at 550°C for 4h. Finally, it is added to 50mL of ammonium fluoride aqueous solution (0.01mol / L), stirred at room temperature for 10h, centrifuged and washed, dried at 100°C overnight, and calcined at 550°C for 4h to obtain HMCM-22 molecular sieve material;

[0144] 26.41g TEOS was added to deionized water, stirred vigorously at room temperature, and then 1.88g concentrated hydrochloric acid was slowly added thereto, stirred at room temperature for 24h, and solution A was obtained; 5.54g aluminum sulfate 18hydrate was dissolved in water, and then 6.04g sodium hydroxide and 3.25g ammonium fluoride were added, and stirred until dissolved to obtain solution B; B was added to A, stirred at room temperature for 24h, and hydrothermal reaction was carried out at 180℃ for 72h. After the reaction, the hydrothermal reaction product was dried and crushed, and calcined at 550℃ for 4h. Subsequently, the obtained solid was added to 50mL ammonium chloride aqueous solution (1mol / L), stirred at 80℃ for ion exchange treatment for 3h, exchanged three times, dried at 100℃ overnight, and calcined at 550℃ for 4h. Finally, the mixture was added into 50 mL of ammonium fluoride aqueous solution (0.01 mol / L), stirred at room temperature for 10 h, washed by centrifugation, dried at 100 °C overnight, and calcined at 550 °C for 4 h to obtain HMOR molecular sieve material.

[0145] 0.15 g of oxide and 0.3 g of molecular sieve material were ground and mixed, and then tableted and granulated into 40-60 mesh to obtain a series catalytic material, which was recorded as catalysts 14-1#, 14-2# and 14-3# according to HBeta, HMCM-22 and HMOR, respectively.

[0146] Embodiment 15

[0147] 5.2217 g of zirconium nitrate pentahydrate and 0.4063 g of indium trichloride were dissolved in 50 mL of ethanol to obtain a mixture, which was dissolved by ultrasound at a frequency of 50 kHz for 30 min, and then 2 mL of dioxane was added and reacted at 20° C. for 40 min to obtain a solution I;

[0148] The solution I was subjected to a hydrothermal reaction at 180°C for 25 hours. After the reaction, the hydrothermal reaction product was dried and crushed, and then calcined at 550°C for 8 hours to obtain powdered InZrO x Oxide materials;

[0149] 20 g of tetrapropylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 14 g of TEOS, 0.145 g of aluminum isopropoxide and 3.25 g of ammonium fluoride, and the mixture was stirred at 30 °C for 12 h to obtain solution II;

[0150] The solution II is subjected to a hydrothermal reaction at 200° C. for 72 hours. After the reaction is completed, the hydrothermal reaction product is dried and crushed, and then calcined at 550° C. for 4 hours to obtain a ZSM-5 molecular sieve material;

[0151] 0.15 g of oxide and 0.3 g of molecular sieve material were ground and mixed, and then granulated into 40-60 mesh to obtain a series catalytic material, which was recorded as catalyst 15#.

[0152] Example 16

[0153] 5.2217 g of zirconium nitrate pentahydrate and 0.5387 g of indium trichloride tetrahydrate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min under a frequency of 50 kHz, 2 mL of dioxane was added and reacted at 20° C. for 40 min to obtain a solution I;

[0154] The solution I was subjected to a hydrothermal reaction at 180°C for 25 hours. After the reaction, the hydrothermal reaction product was dried and crushed, and then calcined at 550°C for 8 hours to obtain powdered InZrO x Oxide materials;

[0155] 20 g of tetrapropylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 14 g of TEOS, 0.145 g of aluminum isopropoxide and 3.25 g of ammonium fluoride, and the mixture was stirred at 30 °C for 12 h to obtain solution II;

[0156] The solution II is subjected to a hydrothermal reaction at 200° C. for 72 hours. After the reaction is completed, the hydrothermal reaction product is dried and crushed, and then calcined at 550° C. for 4 hours to obtain a ZSM-5 molecular sieve material;

[0157] 0.15 g of oxide and 0.3 g of molecular sieve material were ground and mixed, and then pressed into 40-60 mesh granules to obtain a series catalytic material, which was recorded as catalyst 16#.

[0158] Embodiment 17

[0159] 2.1667 g of zirconium oxychloride and 0.2966 g of zinc sulfate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min under a frequency of 50 kHz, 2 mL of epichlorohydrin was added and reacted at 40° C. for 2 min to obtain a solution I;

[0160] The solution I was subjected to a hydrothermal reaction at 100°C for 25 hours. After the reaction was completed, the hydrothermal reaction product was dried and crushed, and then calcined at 600°C for 3 hours to obtain a powdered ZnZrO x Oxide materials;

[0161] 14.4863 g of tetraethylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 10.0943 g of silica sol (40 wt%), 0.0362 g of aluminum oxide and 6.5 g of ammonium fluoride, and the mixture was stirred at 25° C. for 12 h to obtain a solution II;

[0162] The solution II is subjected to a hydrothermal reaction at 180° C. for 48 hours. After the reaction is completed, the hydrothermal reaction product is dried and crushed, and calcined at 500° C. for 4 hours to obtain a ZSM-5 molecular sieve material;

[0163] 0.15 g of oxide and 0.3 g of molecular sieve material were ground and mixed, and then pressed into 40-60 mesh granules to obtain a series catalytic material, which was recorded as catalyst 17#.

[0164] Comparative Example 1

[0165] 4.3230 g of zirconium sulfate tetrahydrate and 0.2966 g of zinc sulfate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min under a frequency of 50 kHz, 2 mL of epichlorohydrin was added and reacted at 25° C. for 2 min to obtain a solution I;

[0166] The solution I was subjected to a hydrothermal reaction at 150°C for 20 hours. After the reaction was completed, the hydrothermal reaction product was dried and crushed, and then calcined at 500°C for 10 hours to obtain a powdered ZnZrO x Oxide materials;

[0167] 14.4863 g of tetraethylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 10.0943 g of silica sol (40 wt%) and 0.0947 g of aluminum chloride, and the mixture was stirred at 25° C. for 12 h to obtain solution II;

[0168] The solution II is subjected to a hydrothermal reaction at 180° C. for 48 hours. After the reaction is completed, the hydrothermal reaction product is dried and crushed, and then calcined at 550° C. for 4 hours to obtain a ZSM-5 molecular sieve material;

[0169] The ZSM-5 material powder (purchased from the catalyst factory of Nankai University, Si / Al=100) was calcined at 550°C for 4h;

[0170] 0.15 g of oxide and 0.3 g of molecular sieve material were ground and mixed, and then pressed into 40-60 mesh granules to obtain a series catalytic material, which was recorded as comparative catalyst 1#.

[0171] Comparative Example 2

[0172] 2.8345 g of zirconium chloride and 0.1685 g of zinc acetate were dissolved in 50 mL of ethanol to obtain a mixture, which was dissolved by ultrasound at a frequency of 50 kHz for 30 min and then reacted at 10° C. for 1 h to obtain a solution I;

[0173] The solution I was subjected to a hydrothermal reaction at 150°C for 20 hours. After the reaction was completed, the hydrothermal reaction product was dried and crushed, and then calcined at 500°C for 4 hours to obtain a powdered ZnZrO x Oxide materials;

[0174] 14.4863 g of tetraethylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 16.1508 g of silica sol (25 wt %), 0.1215 g of aluminum sulfate and 3.25 g of ammonium fluoride, and the mixture was stirred at 25° C. for 12 h to obtain a solution II;

[0175] The solution II is subjected to ZSM-5 molecular sieve material at 180°C;

[0176] 0.15g oxide and 0.3g of the fraction were hydrothermally reacted for 48h. The hydrothermal reaction product was dried and crushed, and calcined at 550°C for 4h to obtain the sub-sieve material, which was ground and mixed, and pressed into 40-60 mesh granules to obtain a series catalytic material, which was recorded as comparative catalyst 2#.

[0177] Comparative Example 3

[0178] 2.8345 g of zirconium chloride, 0.1685 g of zinc acetate and 0.2377 g of indium sulfate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min at a frequency of 50 kHz, 2 mL of epichlorohydrin was added and reacted at 10° C. for 1 h to obtain a solution I;

[0179] The solution I was subjected to a hydrothermal reaction at 150°C for 20 hours. After the reaction was completed, the hydrothermal reaction product was dried and crushed, and then calcined at 500°C for 4 hours to obtain powdered In-ZnZrO x Oxide materials;

[0180] 14.4863 g of tetraethylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 16.1508 g of silica sol (25 wt %), 0.1215 g of aluminum sulfate and 3.25 g of ammonium fluoride, and the mixture was stirred at 25° C. for 12 h to obtain a solution II;

[0181] The solution II is subjected to ZSM-5 molecular sieve material at 180°C;

[0182] 0.15g oxide and 0.3g of the hydrothermal reaction were reacted for 48h. After the reaction, the hydrothermal reaction product was dried and crushed, and calcined at 550°C for 4h to obtain the sub-sieve material, which was ground and mixed, and pressed into 40-60 mesh granules to obtain a series catalytic material, which was recorded as comparative catalyst 3#.

[0183] Comparative Example 4

[0184] 2.8345 g of zirconium chloride and 0.1685 g of zinc acetate were dissolved in 50 mL of ethanol to obtain a mixture, and after ultrasonic dissolution at a frequency of 50 kHz for 30 min, 2 mL of epichlorohydrin was added and reacted at 10° C. for 1 h to obtain a solution I, and then 0.2377 g of indium sulfate was added;

[0185] The solution I was subjected to a hydrothermal reaction at 150°C for 20 hours. After the reaction was completed, the hydrothermal reaction product was dried and crushed, and then calcined at 500°C for 4 hours to obtain powdered In-ZnZrO x Oxide materials;

[0186] 14.4863 g of tetraethylammonium hydroxide and 25.5 mL of deionized water were mixed and stirred for 30 min, followed by the addition of 16.1508 g of silica sol (25 wt %) and 0.1215 g of aluminum sulfate, and the mixture was stirred at 25° C. for 12 h to obtain solution II;

[0187] The solution II is subjected to ZSM-5 molecular sieve material at 180°C;

[0188] 0.15g oxide and 0.3g of the hydrothermal reaction were reacted for 48h. After the reaction, the hydrothermal reaction product was dried and crushed, and calcined at 550°C for 4h to obtain the sub-sieve material, which was ground and mixed, and pressed into 40-60 mesh granules to obtain a series catalytic material, which was recorded as comparative catalyst 4#.

[0189] The oxide / molecular sieve tandem catalytic materials prepared in some embodiments were used to test the performance of catalytic hydrogenation of CO2 gas to produce aromatics. Among them, a micro-fixed bed simulation reaction system was established with a flow rate of 36.0 mL / min and a pressure of 4 MPa for a CO2 / H2 / N2 mixed gas (containing 4% N2, 24% CO2, and 72% H2 in terms of volume percentage). First, before the catalytic activity test, 0.3 g of the catalytic material sample was reduced for 1 hour in a pure H2 gas flow at 320°C and normal pressure, and then a CO2 / H2 / N2 mixed reactant was introduced and pressurized to 4 MPa for evaluation of the catalytic performance. The resulting tail gas components such as CO, CO2, C1-C9 olefins, C1-C9 alkanes, C6-C 10 Aromatic hydrocarbons, methanol and C2-C5 low-carbon alcohols were quantitatively analyzed online by a gas chromatograph equipped with a thermal conductivity detector and a flame ionization detector. The test results of the catalytic performance of the catalytic materials are shown in Table 1.

[0190] Table 1: Catalytic performance test results of oxide / molecular sieve tandem catalytic materials prepared in Examples 1-6, 13-17 and Comparative Examples

[0191]

[0192] From the results in Table 1, it can be seen that the carbon dioxide conversion rate of the above catalytic materials is as high as 19.1%, the aromatics selectivity of most catalytic materials is between 75.2% and 90.2%, the CO selectivity is between 11.3 and 24.3%, and the highest aromatics yield is 15.3%. The catalytic material has excellent carbon dioxide conversion rate and aromatics selectivity / yield, and has low CO selectivity, reflecting excellent catalytic performance of carbon dioxide hydrogenation to aromatics, and the preparation scheme can be flexibly selected according to actual parameter requirements.

[0193] After modification with molecular sieve b-axis regulators such as ammonium fluoride, the b-axis size of the molecular sieve material is effectively controlled. Combined with the preparation strategy of metal oxides, the selectivity and yield of aromatic products are greatly improved.

[0194] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included within the scope of the claims of the present application.

Claims

1. An oxide-molecular sieve tandem catalyst, characterized in that: It includes mechanically mixed metal oxide and molecular sieve, wherein the mass ratio of the metal oxide to the molecular sieve is 1:1-3; The metal oxide includes at least two of zirconium-based oxide, zinc-based oxide, and indium-based oxide, and the mass ratio of each metal oxide is any ratio; the metal oxide is synthesized by a hydrothermal method, and an organic epoxy compound is added during the hydrothermal synthesis of the metal oxide; The molecular sieve is synthesized by a hydrothermal method, and a molecular sieve b-axis regulator is added during the hydrothermal synthesis of the molecular sieve.

2. An oxide-molecular sieve tandem catalyst as claimed in claim 1, characterized in that: The metal oxides include zirconium-based oxides, zinc-based oxides and indium-based oxides, wherein the mass ratio of zirconium, zinc and indium in the zirconium-based oxides, zinc-based oxides and indium-based oxides is 111:6-12:

11.

3. An oxide-molecular sieve tandem catalyst as claimed in claim 1, characterized in that: The zirconium precursor of the zirconium-based oxide is one of zirconium nitrate, zirconium oxychloride, zirconium chloride, zirconium sulfate, zirconium nitrate pentahydrate, zirconium oxychloride octahydrate, and zirconium sulfate tetrahydrate, or a mixture of two or more of them in any proportion; The zinc precursor of the zinc-based oxide is one of zinc nitrate, zinc acetate, zinc sulfate, zinc nitrate hexahydrate, zinc acetate dihydrate, and zinc sulfate heptahydrate, or a mixture of two or more of them in any proportion; The indium precursor of the indium-based oxide is one of indium sulfate, indium acetate, indium trichloride, indium nitrate pentahydrate, indium chloride tetrahydrate, or a mixture of two or more of them in any proportion; The organic epoxy compound is at least one of epichlorohydrin, propylene oxide, butylene oxide, dioxane, and tetrahydrofuran, or a mixture of two or more thereof in any proportion; The molecular sieve b-axis regulator is at least one of ammonium fluoride and behenyltrimethylammonium methyl sulfate or a mixture of the two in any proportion.

4. The oxide-molecular sieve tandem catalyst according to claim 1, characterized in that: The mechanical mixing method is powder mixing, particle mixing or grinding mixing.

5. The oxide-molecular sieve tandem catalyst according to claim 1, characterized in that: The metal oxide is synthesized as follows: The metal oxide precursor is dissolved in a solvent, and an organic epoxy compound is added to react, and a solution I is obtained after the reaction is completed; The solution I is subjected to a hydrothermal reaction, and the hydrothermal reaction product is dried, crushed, and calcined to obtain an oxide material.

6. An oxide-molecular sieve tandem catalyst as claimed in claim 5, characterized in that: The molar ratio of the organic epoxy compound to the metal element of the metal oxide is 1.5-2.5:1; The temperature of the hydrothermal reaction of adding the organic epoxy compound is 10-40°C, and the reaction time is 0-1h; The temperature of the hydrothermal reaction of solution I is 100-200°C, and the reaction time is 15-25h; the temperature of the calcination is 400-600°C, and the time is 3-10h; During the preparation of solution I, if there is an indium-based oxide precursor, the zirconium-based oxide precursor and the zinc-based oxide precursor are added first, and then the organic epoxy compound is added for reaction before adding the indium-based oxide precursor.

7. An oxide-molecular sieve tandem catalyst as claimed in claim 3, characterized in that: The molecular sieve is synthesized as follows: The organic template is added into water, and then the silicon precursor, the aluminum precursor and the molecular sieve b-axis regulator are added to react, and after the reaction is completed, a solution II is obtained; The solution II is subjected to a hydrothermal reaction, and the hydrothermal reaction product is dried, crushed, and calcined to obtain a molecular sieve.

8. An oxide-molecular sieve tandem catalyst as claimed in claim 7, characterized in that: The organic template is one of tetrapropylammonium hydroxide and tetraethylammonium hydroxide or a mixture of the two in any proportion; The silicon precursor is at least one of tetraethyl silicate, 25wt% silica sol and 40wt% silica sol, or a mixture of two or more in any proportion; The aluminum precursor is at least one of aluminum isopropoxide, aluminum sulfate, aluminum chloride and aluminum oxide, or a mixture of two or more of them in any proportion.

9. An oxide-molecular sieve tandem catalyst as claimed in claim 7, characterized in that: In terms of molar ratio, the ratio of the organic template, the molecular sieve b-axis regulator, the Si element in the silicon precursor, and the aluminum element in the aluminum precursor is 130-160:0-160:100:1; the temperature for the mixed reaction is 10-40°C, and the reaction time is 6-18h; The temperature of the hydrothermal reaction of solution II is 150-220° C., and the reaction time is 24-96 hours; the temperature of the calcination is 500-600° C., and the time is 3-10 hours.

10. Use of the oxide-molecular sieve tandem catalyst according to any one of claims 1 to 9 in the preparation of aromatics by reduction of carbon dioxide, characterized in that: The CO2 conversion rate is not less than 11.9%, the CO selectivity is not higher than 24.3%, and the aromatics selectivity is not less than 75.2%.